2020
DOI: 10.1109/access.2020.3003049
|View full text |Cite
|
Sign up to set email alerts
|

Supervised Learning Approach for State Estimation of Unmeasured Points of Distribution Network

Abstract: This paper presents a new approach to state estimation (SE) of distribution networks, which becomes more complex when there is lack of monitoring. Several studies have been carried out on SE to compensate for the lack of monitoring; however, the observability of the distribution system is poor compared to the transmission system. In the proposed approach, the representative load profile and the electricity charges of consumers are required to obtain the load profile of each consumer. In addition, the uncertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…As several datasets were synthetically generated using simulation software, only various studies reported problems with imbalanced datasets and missing items in the data. In this regard, Hong et al [45] analyzed the case in which data were missing from one of the buses, concluding that system performance decreased significantly. Karagiannopoulos et al [46] extrapolated historical data and used information from the public domain or from neighboring systems to deal with missing or noisy data.…”
Section: Discussionmentioning
confidence: 99%
“…As several datasets were synthetically generated using simulation software, only various studies reported problems with imbalanced datasets and missing items in the data. In this regard, Hong et al [45] analyzed the case in which data were missing from one of the buses, concluding that system performance decreased significantly. Karagiannopoulos et al [46] extrapolated historical data and used information from the public domain or from neighboring systems to deal with missing or noisy data.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial neural networks or connectionist systems are machine learning tools inspired by biological neural networks and can process the same data as the human brain [22]. ANN can develop linear and nonlinear models for time series.…”
Section: Feed-forward Neural Networkmentioning
confidence: 99%
“…A gradient-based multi-area algorithm is proposed for the distribution network state estimation, and it is expressed through a weighted least squares problem in [10]. The authors of [11], proposed a methodology to estimate the target bus voltage with known bus information using a supervised learning algorithm. A neural network technique that offers robustness for any restructuring in the network topology discussed in [12].…”
Section: Introductionmentioning
confidence: 99%